Study of the forward photons productions in pp collisions at sqrts = 7 TeV with the ZDC detector of the ATLAS experiment - Monzani, Simone <1981> (Alma Mater Studiorum - Università di Bologna, 2013)
The Zero Degree Calorimeter (ZDC) of the ATLAS experiment at CERN is placed in the TAN of the LHC collider, covering the pseudorapidity region higher than 8.3. It is composed by 2 calorimeters, each one longitudinally segmented in 4 modules, located at 140 m from the IP exactly on the beam axis. The ZDC can detect neutral particles during pp collisions and it is a tool for diffractive physics. Here we present results on the forward photon energy distribution obtained using p-p collision data at sqrts = 7 TeV. First the pi0 reconstruction will be used for the detector calibration with photons, then we will show results on the forward photon energy distribution in p-p collisions and the same distribution, but obtained using MC generators. Finally a comparison between data and MC will be shown.